The dynamics of core and periphery in the European monetary union: A new approach. (April 2021) - Campos, Nauro F.; Macchiarelli, Corrado
Highlights: We offer a new (continuous and dynamic) approach to study core-periphery in the EMU. We provide novel results for a set of European countries using yearly data from 1960. We use OCA theory to unveil the main explanatory factors of these dynamics. We find the emergence a newer core, an intermediate and a periphery set of countries. Euro membership and competition make countries more likely to be in the core. Abstract: Despite numerous studies about core-periphery in monetary unions, few focus on their dynamics. This paper (i) presents new theory-based, continuous and dynamic measures of the probability of a country being classified as core or periphery; (ii) estimates the determinants of the changes in this probability over time and across countries; and (iii) uses the Phillips-Sul convergence panel framework to investigate the behaviour of core and periphery groups over time. Our main results indicate that the post-EMU decrease of the core-periphery gap that we document was mainly driven by the adoption of the euro and by increasing competition (lower mark-ups).